Continuous Glucose Monitoring (CGM) as a Behavior Modification Tool: A Case Series on CGM-Guided Nutrition in People With Type 2 Diabetes Not Using Insulin. - Ettestad, Tara M.; Willis, Holly J.; Johnson, Elizabeth; Green, Courtney R.; Bergenstal, Richard M. (Clinical Diabetes)
The article focuses on the role of continuous glucose monitoring (CGM) systems in managing type 2 diabetes through lifestyle modifications and dietary changes. It highlights that over 500 million people globally have diabetes, with type 2 diabetes being the most prevalent form. The American Diabetes Association recommends lifestyle changes as a primary treatment approach, and CGM devices can provide real-time data to help individuals understand how their food choices and physical activities affect their glucose levels. The article presents several case studies demonstrating how CGM use led to significant improvements in glycemic control and lifestyle habits among individuals with type 2 diabetes, emphasizing the importance of collaboration between patients and healthcare providers in achieving these outcomes.